Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/724208
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Self‐Reported Chronic Bronchitis in a Canadian Population: The Canadian Community Health Survey, 2007 To 2008

Abstract: The results suggest an association between ethnicity and the prevalence of CB. The associations between self-reported CB prevalence and household income, educational attainment and smoking status varied according to region of Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
0
5
1
Order By: Relevance
“…In addition, the prevalence of asthma and asthma-like symptoms in urban communities of Beijing has been reported to be higher than that in rural Beijing (14). The prevalence of CB in our study was 6.9%, which is higher than that in Canada (2.5%), India (3.5%), Iran (5.6%), Vietnam (5.6%), and Australia (6.1%) (15)(16)(17)(18)(19), but lower than that in European countries such as Sweden (7.2%) and Turkey (14.1%) (20,21). Chronic cough and chronic phlegm are symptoms associated with CB.…”
Section: Discussioncontrasting
confidence: 61%
“…In addition, the prevalence of asthma and asthma-like symptoms in urban communities of Beijing has been reported to be higher than that in rural Beijing (14). The prevalence of CB in our study was 6.9%, which is higher than that in Canada (2.5%), India (3.5%), Iran (5.6%), Vietnam (5.6%), and Australia (6.1%) (15)(16)(17)(18)(19), but lower than that in European countries such as Sweden (7.2%) and Turkey (14.1%) (20,21). Chronic cough and chronic phlegm are symptoms associated with CB.…”
Section: Discussioncontrasting
confidence: 61%
“…In Canada, the prevalence of CB in adults was 2.5%. 1 However, in India, the prevalence among the individuals aged ≥40 years was higher compared to the individuals aged <40 years ( 10% vs. 8.5%). 23 A survey in Finland showed that during the last 3 decades (between 1986 and 2007), the prevalence of CB decreased from 19% in 1982 to 13% in 2007 (P for trend <0.001).…”
Section: Resultsmentioning
confidence: 93%
“…Chronic bronchitis (CB) implies the chronic inflammation of the bronchi which causes the swelling and irritation of the respiratory pathways as well as increased mucus production. 1 It does not necessarily imply the presence of infection. 2 CB is a common disease among the general population, especially among the middle-aged and elderly groups.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the 2002/03 First Nations Regional Longitudinal Health Survey reported that age-standardized prevalence of self-reported, doctor-diagnosed CB was 3.7% in First Nations living on-reserve [4]. All these rates are higher than the prevalence of 2.4 and 2.5% found in the non-Aboriginal Canadian population, according to the 2005 CCHS and 2007/2008 CCHS, respectively [5, 25]. A recent study of Saskatchewan rural residents (excluding Aboriginal residents) reported a prevalence of 5.9% [26].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to environmental tobacco smoke (household smoke) is the most important risk factor for the development of CB as reported by several studies [ 2 , 25 – 29 ]. The current study did not report a significant association between personal non-traditional use of tobacco and the prevalence of CB; however, there was a significant interaction with environmental tobacco smoke and BMI.…”
Section: Discussionmentioning
confidence: 99%